Effect Of Chalcopyrite And Pyrrhotite Interaction On Flotation Separation - X. Cheng (Society for Mining, Metallurgy & Exploration, 1992)
A series of batch flotation tests was performed on chalcopyrite-quartzite, pyrrhotite-quartzite, and on chalcopyrite-pyrrhotite-quartzite mixtures. Pulp potential measurements in the flotation tests of single sulfide minerals indicated that each sulfide mineral had its own optimum potential range for flotation. When these results were used to select the potential ranges for the separation of the two minerals from their mixture, their flotation responses changed and the selectivity of separation was adversely affected. A possible mechanism involving surface alteration through galvanic interaction is discussed. A method to improve the selectivity of flotation separation was proposed.